Karakteristik Komplikasi Luaran Janin dan Ibu Hamil yang Menderita Early Onset Preeclampsia (EOPE) dan Late Onset Preeclampsia (LOPE) yang Diterminasi di RSUD Raden Mattaher Jambi - Arini Putri Antika; Zul Andriatha; Firmansyah Firmansyah; Attiya Istarini; Erny Kusdiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Preeclampsia is a condition of hypertension occurring after 20 weeks of gestation, accompanied by organ dysfunction and proteinuria. Preeclampsia is classified into Early Onset Preeclampsia (EOPE), which occurs before 34 weeks of gestation, and Late Onset Preeclampsia (LOPE), which occurs after 34 weeks of gestation. EOPE carries a higher risk of maternal and fetal complications compared to LOPE. This research aims to analyze the complications in mothers and fetuses with EOPE and LOPE that were terminated at RSUD Raden Mattaher Jambi between 2020 and 2022. This descriptive research was conducted in the Medical Records Department of RSUD Raden Mattaher, Jambi, involving 82 patients who experienced both maternal and fetal complications with EOPE and LOPE that were terminated. Sampling was carried out using the total sampling technique based on inclusion and exclusion criteria. The results of this research showed that the prevalence of EOPE was 69.5%, while LOPE accounted for 30.5%. Maternal complications were more commonly found in EOPE cases, including eclampsia (42.1%), HELLP syndrome (36%), premature rupture of membranes (14%), placental abruption (14%), and maternal mortality (5.3%). Fetal complications in EOPE included Respiratory Distress Syndrome (RDS) (10.5%), prematurity (26.3%), low birth weight (29.8%), Intrauterine Growth Restriction (IUGR) (10.5%), and Intrauterine Fetal Death (IUFD) (1.8%). The perinatal mortality rate in EOPE was 7%, with asphyxia recorded in 12.3% of cases. EOPE is more frequently encountered than LOPE and is associated with more severe maternal and fetal complications. Early detection and management of EOPE are crucial to reducing complications and improving pregnancy outcomes.